2020
DOI: 10.1016/j.ejca.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

A closer look at immune-mediated myocarditis in the era of combined checkpoint blockade and targeted therapies

Abstract: term benefit. Clinical vigilance, prompt multimodal diagnosis and multidisciplinary management are paramount for the treatment of immune-mediated myocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 38 publications
0
42
0
5
Order By: Relevance
“…However, clear consensus on the optimal dose of corticosteroids (the first-line treatment to start as an immunosuppressive) and on how and when to add other immunosuppressive agents has not been reported yet. In this regard, the initial dose of corticosteroid [(methyl) prednisolone] is usually recommended as 1–2 mg/kg in the present study ( 6 , 7 , 9 ). Some studies showed strong association of high-dose steroid therapy with a significantly lower rate of major adverse cardiac events ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, clear consensus on the optimal dose of corticosteroids (the first-line treatment to start as an immunosuppressive) and on how and when to add other immunosuppressive agents has not been reported yet. In this regard, the initial dose of corticosteroid [(methyl) prednisolone] is usually recommended as 1–2 mg/kg in the present study ( 6 , 7 , 9 ). Some studies showed strong association of high-dose steroid therapy with a significantly lower rate of major adverse cardiac events ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical presentation generally ranges from an asymptomatic elevation of cardiac enzymes to sudden death due to heart failure. Accordingly, symptoms generally present with a heterogeneous clinical spectrum that might include dyspnea (usually accompanied by a reduced left ventricular ejection fraction (LVEF) value), palpitations, nausea, fatigue, weight loss, and chest pain ( 6 ). In full-blown cases, all aspects of an acute heart failure scenario are usually fully established.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations